Effects of flower and fruit extracts of Melastoma malabathricum Linn. on growth of pathogenic bacteria: Listeria monocytogenes, Staphylococcus aureus, Escherichia coli, and Salmonella typhimurium - Che Omar, Siti Nurhadis; Abdullah, Janna Ong; Khairoji, Khairul Anuar; Sieo, Chin Chin; Hamid, Muhajir (Hindawi Publishing Corporation, 2013)
Melastoma malabathricum Linn. is a shrub that comes with beautiful pink or purple flowers and has berries-like fruits rich in anthocyanins. This study was carried out with the aim to evaluate the inhibitory activities of different concentrations of the M. malabathricum Linn. flower and fruit crude extracts against Listeria monocytogenes IMR L55, Staphylococcus aureus IMR S244, Escherichia coli IMR E30, and Salmonella typhimurium IMR S100 using the disc diffusion method. The lowest concentrations of the extracts producing inhibition zones against the test microorganisms were used to determine their minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs). In addition, the growth of Listeria monocytogenes IMR L55 and Staphylococcus aureus IMR S244 grown in medium supplemented with the respective extracts at different temperatures (4°C, 25°C, and 37°C) and pHs (4, 6, 7, and 8) was determined.